Magnesium hexacyanoferrate nanocatalysts attenuate chemodrug-induced cardiotoxicity through an anti-apoptosis mechanism driven by modulation of ferrous iron - Minfeng Huo; Zhimin Tang; Liying Wang; Linlin Zhang; Haiyan Guo; Yu Chen; Ping Gu; Jianlin Shi (Nature Communications, 2022)
Doxorubicin is commonly used in cancer chemotherapy, but its cardiotoxicity from iron overload is one of the severe side effects. Here, the authors prepare magnesium hexacyanoferrate nanocatalysts to capture excess ferrous species and eliminate cytotoxic radical species in vitro and in vivo.